Origin of the spectral red-shift and polarization patterns of self-assembled InGaN nanostructures on GaN nanowires. Issue 15 (29th March 2023) - Ries, Maximilian; Nippert, Felix; März, Benjamin; Alonso-Orts, Manuel; Grieb, Tim; Hötzel, Rudolfo; Hille, Pascal; Emtenani, Pouria; Akinoglu, Eser Metin; Speiser, Eugen; Plaickner, Julian; Schörmann, Jörg; et al.
Abstract : A pronounced polarization anisotropy and spectral red-shift of the emission wavelength of individual InGaN nanowires is attributed to the spontaneous formation of superlattices caused by inhomogeneous In-distribution in the wires. Abstract : The luminescence of In x Ga1− x N nanowires (NWs) is frequently reported with large red-shifts as compared to the theoretical value expected from the average In content. Both compositional fluctuations and radial built-in fields were considered accountable for this effect, depending on the size, structure, composition, and surrounding medium of the NWs. In the present work, the emission properties of InGaN/GaN NWs grown by plasma-assisted molecular beam epitaxy are investigated in a comprehensive study combining ultraviolet-Raman and photoluminescence spectroscopy (PL) on vertical arrays, polarization-dependent PL on bundles of a few NWs, scanning transmission electron microscopy, energy-dispersive X-ray spectroscopy, and calculations of the band profiles. The roles of inhomogeneous In distribution and radial fields in the context of optical emission properties are addressed. The radial built-in fields are found to be modest, with a maximum surface band bending below 350 meV. On the other hand, variations in the local In content have been observed that give rise to potential fluctuations whose impact on the emission properties is shown to prevail over band-bending effects. Two luminescence bands with large positive and moderate negative polarization ratios of ≈+80% and ≤−60%, respectively, were observed. The red-shift in the luminescence is associated with In-rich inclusions in the NWs due to thermodynamic decomposition during growth. The negative polarization anisotropy is suggested to result from spontaneously formed superlattices in the In-rich regions of the NWs. The NWs show a preferred orthogonal absorption due to the dielectric boundary conditions and highlight the extreme sensitivity of these structures towards light polarization.